Child abuse its implications for health education - Mejillano, Evelina A. (Education quarterly.)
For the teacher, school nurse and other school personnel who wish to get involed and assume a leadership role in child abuse and neglect, the opportunities are limitless. They can assist the development of educational policies and procedures. They can spearhead a public awareness campaign, organize consultation teams, design training programs for parents at risk, coordinate community resources and develop political support to prevent child abuse and neglect. With these committed individuals at the center point, it will be only a matter of time until the school and community will have a broad based prevention program.